EFFECT OF SOLUS PER AQUA (SPA) ON INFANT WEIGHT - Agrystina Ryma Melati; C Tjahjono Kuntjoro; Sri Sumarni; Kamilah Hidayati; Rr. Sri Endang Pujiastuti (Belitung Nursing Journal, 2017)
Background: The prevalence of skinny infants in Indonesia is still high. Baby's spa is considered to be able increase infant’s weight. Objective: To determine the effect of baby spa in infant weight in in Bebengan Village, Boja Sub District, Kendal Regency, Central Java, Indonesia. Methods: This study was a quasi-experimental study with non-equivalent control group design. There were 38 infants were selected using purposive sampling, divided into three groups, namely: 1) a group received spa two times per week (12 infants), 2) a group received spa three times per week (13 infants), and 3) a control group. Baby digital scale of ARN-EBSD-04 was used to measure infant weight. Data were analyzed using paired t-test and ANOVA. Results: There was statistically significant effect of intervention in each group on the infant’s weight. However, the data showed that the intervention that had a better effect on infant weight was the intervention of spa in two times per week with mean difference before and after intervention of 603 g. Conclusions: Doing spa two times per week could significantly increase infant weight effectively. Therefore, it is recommended for midwife to apply this intervention to increase the weight gain of babies and to reduce the number of skinny infants in Indonesia.